Comparative Immune Responses and Cytokine Gene Expressions in Sheep Vaccinated with Brucella abortus RB51 Vaccine and Brucella melitensis Rev. 1 Vaccine - Ramy F. Ghobrial; Samar M. Atwa; Mohamed el Beskawy; Verginia M. Farag; Mohamed Eisa; Doaa Naguib; Mohamed EL-Diasty (Journal of Advanced Veterinary Research, 2023)
Â  This work applied three Brucella vaccination protocols in adult Brucella-free ewes. Serum and blood samples were collected from each group at time points 0, 7, 14, 21, 28, and 60 days post-vaccination. In addition, the humoral immune response was assessed by the Rose Bengal Plate test (RBPT) every week for 16 weeks. Also, cell-mediated immunity was evaluated. Additionally, interleukin 6 (IL-6) and tumor necrosis factor-alpha (TNF- Î±) were assessed. The results indicated that the cellular immune responses induced by the B. abortus RB51 vaccine with a dose of 3.4 x1010 provide a protective immune response near the effect produced by the B. melitensis Rev. 1 vaccine. Moreover, the IL-6 was expressed significantly less in the RB51- vaccinated group with a dose of 1.7 x1010 CFU (1 ml subcutaneously), greater in the Rev. 1-vaccinated group with a dose of 1.6 Ã— 109 CFU (1 ml subcutaneously), and highest expression in the RB51-vaccinated group with a dose of 3.4 x1010 CFU ( 2 ml subcutaneously). Also, the expression of TNF- Î± was lowest in the group vaccinated with RB51 vaccine with a dose of 1.7 x1010 CFU, with greater abundance in the group vaccinated with Rev. 1 vaccine and highest expression in the group vaccinated with RB51 vaccine with a dose of 3.4 x1010 CFU. These findings imply that the RB51 vaccine, given to sheep with a dose of 3.4 x 1010 CFU, may trigger protective immune responses and be applied in the field to control brucellosis in sheep.